Analisis Yuridis terhadap Keabsahan Perkawinan Sesama Jenis antar Warga Negara Indonesia di Luar Negeri dalam Perspektif Hukum Perdata Internasional - Nugroho, Lucky Dafira; Murbarani, Tanissa Diva Siti; Rahayu, Ervina Dwi (Lembaga Yasin AlSys, 2025)
This study examines the validity of same-sex marriages conducted by Indonesian citizens (WNI) abroad from the perspective of Private International Law (Hukum Perdata Internasional, HPI). The phenomena of globalization and the legalization of same-sex marriage in several countries have created opportunities for Indonesian citizens to marry in jurisdictions recognizing such unions. However, this raises normative conflicts with Indonesia’s national legal system, which only recognizes marriages between a man and a woman based on Articles 1 and 2 of Law No. 1 of 1974 in conjunction with Law No. 16 of 2019. The research employs a normative juridical approach through legislative analysis and comparative law. The findings indicate that although same-sex marriages between Indonesian citizens are considered valid under the law of the country where the marriage is celebrated (lex loci celebrationis), Indonesia rejects them based on the public order principle (ordre public) due to conflicts with national religious and cultural values. This rejection results in the inability to register such marriages civilly, the loss of inheritance rights, and legal ambiguity regarding the status of children born from or adopted by same-sex couples. The study’s implications underscore the importance of restructuring regulations to ensure the protection of citizens’ fundamental rights without compromising national legal principles. Furthermore, the research contributes to the development of transnational family law concepts and clarifies the selective role of Private International Law in filtering foreign laws that conflict with domestic norms.